World of Warcraft : an autoethnography of an English language learner's foreign language acquisition through gaming (2024)
Playing a digital video game, or gaming, has become a relevant topic in second and foreign language acquisition (SLA) because it represents an appealing way of acquiring knowledge and skills in relation to it. Different research methodologies have been used to investigate how language learners can learn a language through gaming, most of them carried out as qualitative research collecting data from focal groups through observation, field notes, surveys and interviews. However, there are limited studies on SLA and gaming developed from a learner’s introspective and retrospective point of view and with the employment of autoethnographic narrative as a data collection tool. Narratives are useful qualitative methods that help to reconstruct and reflect on experiences to critically comprehend the processes of learning and their impact on the student’s educational process (Bolivar et al., 2001). This qualitative study employs a narrative autoethnography to describe my experience acquiring English as a foreign language through the video game World of Warcraft and how it helped me develop an array of language skills and motivation towards English and contributed to shape my identity while I played it for about ten years. The study’s results demonstrate how I improved my English through this video game from A2 to B2 in accordance with the CEFR. It also provides insights into our understanding of online gaming as a tool for mastering English because of the role of interaction and the fostering of motivation that it brings due to its competitive nature. Finally, it highlights the impact it may have into the formation of the identity in young learners.